TINJAUAN HUKUM AKTA PENGANGKATAN ANAK BERDASARKAN DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA SAMARINDA - Rima Devina (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT Pregnant women are married to a woman who is pregnant out of wedlock, whether married to a man who impregnates her or by a man who does not impregnate her. Therefore, the problem of marrying a pregnant woman requires careful and prudent attention, especially by a marriage registrar employee. This is meant by the existence of a social phenomenon regarding the lack of awareness of the Muslim community towards the moral, religious and ethical principles of the occurrence of a man who does not impregnate him but he marries him.In Law No. 1 of 1974 no one regulates guardianship of children due to the marriage of pregnant women. Therefore the provisions of guardianship according to Law No. 1 In 1974 while the child was born in a marriage that was deemed valid by the state, his guardianship was with the two legitimate parents. Because in Law No. 1 of 1974 does not regulate the distribution of inheritance rights, but if the child is considered legal according to Law No. 1 Year 1974 automatically the child gets inheritance from the lineage of his father and mother.